Peningkatan Partisipasi Siswa Kelas IV Dalam Pembelajaran IPS Melalui Model Picture And Picture - Yuvardita Habibi (Universitas Negeri Padang, 2021)
This study aims to describe implementation of picture and picture model at SDS Al-Azhar Bukittinggi. The method was used in this research is Classroom Action Research. Data were collected through observation, interview, and test. Data were analyzed descriptively. The results of the research are implementation of Picture and Picture model can increased student participation, it can be look by student’s activity in asking and answering teachers question. Implication of the this research is the creation of a new model to use new model on learning activities in teacher class. Recommendations research is the picture and picture model should be studied seriously by teachers before applying this model.